An Optimization of Sugarcane Bagasse Ratio for Eco-icebox Composite - Raja Sehar, Shasmitra; Hashim, Nor Haslina (Progress in Engineering Application and Technology, 2023)
Non-biodegradable wastes are one of major global concern. Large percentage of non-biodegradable wastes are polystyrene food storing packages and containers. Non-biodegradable materials like plastics and polystyrene becomes one of necessary thing that people can’t live without it. The uses of non-biodegradable materials increase, the generation of polymer solid waste of the country increases that reflect the increases in the rate of air pollution, land pollution, water pollution, environment and health risks. This is because polystyrene wastes need to undergoes incineration process to dispose from the earth surface. This project aims to produce an eco-icebox (SBCEI) made of sugarcane bagasse and fenugreek seed powder and the SBCEI characterized in term of thermal conductivity, tensile strength, density and water absorption to replace polystyrene icebox in the market. Firstly, the bagasse waste was collected and pretreated with 10% NaOH, oven dried and grinded into small particles. The bagasse was tested for tensile strength using Universal Testing Machine. Followed by the fenugreek seeds were roasted and grinded into powder form for the sample making. The powdered fenugreek seed was tested for solubility and pH using hot plate and litmus paper. The composite samples with three different ratios R1 (1:1:3), R2((2:1:3) and R3(3:1:3) in same size of bagasse, fenugreek seed powder and water were prepared, dried and tested for tensile strength using Universal Testing Machine, thermal conductivity using hot plate, density and water absorption using weighing balance. The thermal conductivity of polystyrene was 19.53 W/mK and the tensile strength was 6.011 N/m2. Thermal conductivity of R1, R2 and R3 were 19.71 W/mK, 20.05 W/mK and 20.67 W/mK respectively. R1 composite have slightly high thermal value than polystyrene that shows it a poor heat conductor. The tensile strength of R1, R2 and R3 were 91.981 N/m2, 59.859 N/m2 and 55.079 N/m2 respectively. This result shows bagasse composites have strength to withstand the tensile forces compared to polystyrene. However, density of SBCEI R1, R2 and R3 were 1.1107 g/cm3, 1.1162 g/cm3 and 1.1185 g/cm3 respectively. Nevertheless, the result was compared with polystyrene data. In this study, the polystyrene presents better data compared to SBCEI in terms of water absorption and density. Therefore, optimization of the ratio would be a better choice to improve the product characteristics in the future.